IMPACT DIFFERENTIATION OF THE SILICATE AND ORE MATERIAL OF THE PROTOCRUST - Rekharskiy V.I.; Dikov Yu.P.; Mukhin L.M.; Gerasimov M.V. (My University, 1990)
Since the accretion model is now generally accepted in the current cosmogony of the planets, the problem of the transformation of their material amounts to determining the main mechanism of accumulation, with all the consequences following from it. Analysis of the geologic, petrologic and geochemical data on these stages of development of the Earth and the other terrestrial planets suggests that the most adequate hypothesis is that of the mechanism of impact differentiation of the protoplanetary substance, We wish to call attention to the most important features of impact differentiation of the material, features that are of fundamental significance for understanding the behavior of the rock-forming and ore elements in the very earliest and subsequent stages of the Earth's history. The data presented enable us to state that the generation and development of the silicate and silicate-fluid systems, and the mobilization and concentration of ore elements, occurred during the formation of a petrochemically and geochemically inhomogeneous protocrust even in the very earliest - the accretional - stage of the Earth's evolution. This stage, at least in its concluding phases, can with full justification be considered the initial stage of geologic history.